RETRACTED: The modeling of the tectonic state of the angren coal mine Area before mining operations - Sayyidkosimov Sayyidjabbor; Sokhibov Isomiddin; Anarbayev Khalimjon (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001